PENGARUH ONLINE PURCHASE RETURN POLICY LENIENCY TERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI OLEH KEPERCAYAAN KONSUMEN ONLINE SHOP TOKOPEDIA DI KOTA BANDA ACEH - M. Alam Mufid; Mukhlis Yunus (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This study aims to measure the effect of online purchase return policy leniency on buying decision and consumer trust as the mediation at consumers of Tokopedia in Banda Aceh. The sample used in this study is consumers of Tokopedia in Banda Aceh with total of 130 respondents. Data collection equipment used in this study was a questionnaire and the sampling technique used was purposive sampling. Hierarchical Linear Modelling (HLM) was used as themethod of analysis to determine the effect of all the variables involved. Based on the results of the HLM analysis indicated that online purchase return policy leniency was related to buying decision, online purchase return policy leniency significantly influence consumer trust, consumer trust was related to buying decision, consumer trust partially mediated the relationship between online purchase return policy leniency and buying decision.Keywords: Online purchase return policy leniency, buying decision, consumer trust, Hierarchical Linear Modelling.